New insights on the cardiovascular effects of IGF-1 - Macvanin, Mirjana; Gluvic, Zoran; Radovanovic, Jelena; Essack, Magbubah; Gao, Xin; Isenovic, Esma R. (Frontiers in Endocrinology, 2023)
Cardiovascular (CV) disorders are steadily increasing, making them the world’s most prevalent health issue. New research highlights the importance of insulin-like growth factor 1 (IGF-1) for maintaining cardiovascular health. IGF-1, an anabolic growth hormone, regulates cell division, proliferation, and survival. In addition to its well-known growth-promoting and metabolic effects, there is mounting evidence that IGF-1 plays a specialized role in the complex activities that underpin cardiovascular function. IGF-1 promotes cardiac development and improves cardiac output, stroke volume, contractility, and ejection fraction. In addition, IGF-1 mediates many growth hormones (GH) actions. IGF-1 stimulates contractility and tissue remodeling in humans to improve heart function after myocardial infarction. IGF-1 also improves the lipid profile, lowers insulin levels, increases insulin sensitivity, and promotes glucose metabolism. These findings point to the intriguing medicinal potential of IGF-1. Human studies associate low serum levels of free or total IGF-1 with an increased risk of CV and cerebrovascular illness. Extensive human trials are being conducted to investigate the therapeutic efficacy and outcomes of IGF-1-related therapy. We anticipate the development of such novel IGF-1-related therapy with minimal side effects. This review discusses recent findings on IGF-1’s role in the cardiovascular system, both in normal and pathological conditions. We provide insights on the epigenetic regulation of IGF-1 mediated by microRNAs and discuss progress in therapeutic interventions aiming to target the IGF axis.